TRANSFORMING AMERICAN SCIENCE universities, the government, and the cold war. - Engel, Jonathan ([S.l.] : ROUTLEDGE, 2023)
Transforming American Science documents the ways in which federal funds catalyzed or accelerated changes in both university culture and the broader system of American higher education during the post-World War II decades. The events of the book lie within the context of the Cold War, when pressure to maintain parity with the Soviet Union impelled more generous government spending and a willingness of some universities to reorient their missions in the service of country and of science. The book draws upon a substantial amount of archival research conducted in various university archives (MIT, Berkeley, Stanford) as well as at the Library of Congress, the National Archives, and various presidential libraries. Author Jonathan Engel considers the repurposing of the wartime Manhattan Engineering District and the Office of Naval Research to robust peacetime roles in supporting the nation's expanding research efforts, along with the birth of the National Science Foundation, space exploration, and atoms for peace among other topics. This volume is the perfect resource for all those interested in Cold War history and in the history of American science and technology policy.
Keywords: Research -- United States -- History -- 20th century; Research institutes -- United States -- History -- 20th century; Federal aid to research -- United States -- History -- 20th century; Science and state -- United States -- History -- 20th century; Technology and state -- United States -- History -- 20th century; HISTORY / Modern / 20th Century; HISTORY / United States / 20th Century